Multiple targets related to mitochondrial function unveiled by metabolomics and proteomics profiles of hearts from atrial fibrillation patients - Liu, Weizhuo; Hu, Bo; Wang, Yuliang; Zhang, Xiaobin; Zhu, Miao; Shi, Yu; Guo, Changfa; Zhang, Yangyang (Frontiers in Physiology, 2023)
The prominent mitochondrial metabolic changes of the atrium reportedly have significant impact on electrical signals and structural remodeling which play important roles in the occurrence and development of atrial fibrillation (AF). However, the mechanism is not completely known. The objective of this study was to explore the mitochondrial metabolism reprogrammed in AF patients by integrating metabolomics as well as proteomics of human atrium tissues. Left atrial tissue samples were harvested from 10 non-valvular AF patients and 10 matched samples from healthy donors for transplantation. In metabolomics analysis, 113 metabolites were up-regulated and 10 metabolites were down-regulated in AF, where multiple pathways related to mitochondrial energy metabolism were enriched. Correlation analysis between the differentially expressed proteins and metabolites identified several hub proteins related to mitochondrial function including Glycerol-3-phosphate dehydrogenase 2 (GPD2), Synemin (SYNM), Plectin (PLEC), with MCC score of 27, 17, 16, respectively, which have the most interactions with the dysregulated metabolites and ranked at the top in network string interactions scored by MCC method. All 330 differentially expressed proteins including 225 up-regulated and 105 down-regulated molecules were revealed and analyzed, which identified the down-regulation of GPD2 (p=0.02 and FC=0.77), PLEC (p< 0.001 and FC= 0.71) and SYNM (p= 0.04 and FC= 0.76) in AF patients. Gene Set Variation Analysis (GSEA) showed mitochondrial metabolism-associated pathways including oxidative phosphorylation (NES: -1.73) and ATP biosynthetic process (NES: -2.29), were dramatically diversified in human AF. In GSVA, the expression levels of GPD2, PLEC and SYNM were demonstrated to be associated with multiple metabolic pathways related to mitochondrial function (e.g., lipid metabolism and AMP activated protein kinase signaling) and cardiac structural and electrical remodeling (e.g., contractile fiber, ion homeostasis), which were proven vital in the development and maintenance of AF. In all, this study provides new insights into understanding the mechanisms of AF progression, especially the reprogramming mitochondrial metabolism, and identifies several genes related to mitochondrial function as novel targets for AF, which may be involved in the occurrence and development of AF.